Electromagnetic calorimeter for Belle II. (13th February 2015) - Belle-ECL,; Aulchenko, V; Bobrov, A; Bondar, A; Cheon, B G; Eidelman, S; Epifanov, D; Garmash, Yu; Goh, Y M; Kim, S H; Krokovny, P; Kuzmin, A; et al.
Abstract: The electromagnetic calorimeter of the BELLE II detector for experiments at Super B-factory SuperKEKB is briefly described. The project of the calorimeter upgrade to meet severe background conditions expected at the upgraded KEK B factory is presented.